Community Empowerment in Household Clean and Healthy Behavior (PHBS), especially for Prevention and Early Action on Infectious Diseases and Cerebrocardiovascular Diseases in Pekan Village, Tanjung Beringin District, Serdang Bedagai - Arina, Cut Aria; Rusdiana, Rusdiana; Andra, Cut Aryfa; Andriyani, Yunilda; Ginting, Yehezkiel (ABDIMAS TALENTA: Jurnal Pengabdian Kepada Masyarakat, 2023)
Infectious diseases, especially those transmitted by mosquitoes, are health problems that are often experienced by people in coastal areas. Cases of infection such as dengue hemorrhagic fever (DHF) and even malaria, were reported to be found in partner areas. The partner's location which is located on the beach with swamps around it allows breeding places for mosquitoes, especially Anopheles sp. which acts as the main vector of malaria and filarial. Breeding sites for Aedes aegypti and Aedes albopictus mosquitoes as dengue vectors are also possible to be found in partner locations because they are located not too far from the city of Medan and include tourist attractions. Cerebrocardiovascular disease, especially stroke and coronary heart, has high morbidity and mortality rates. This disease has almost the same risk factors because both are related to blood vessels, five main risk factors can be controlled, namely hypertension, diabetes mellitus, dyslipidemia, obesity, and smoking. The importance of public understanding of how to prevent and control these risk factors. Public Health Clinic Center as a front-line health service facility plays an important role in improving the health status of the community. One of the community service activities carried out by the Tanjung Beringin Health Center is counseling to cadres from community members this is related to stroke and coronary heart disease because these diseases are diseases that have a very close relationship and become a problem that requires proper and careful management. The risk factors for these two diseases, including hypertension, cause heart attacks, heart failure, and strokes and often lead to new DM in many cases. Due to the increase in the disease due to lifestyle changes, with this education, we can add to the public's knowledge to be responsive in conducting treatment and regular health checks.